Legends and lives of saints : Publications for children and youth in Poland in 1945-1949 - Lewandowicz-Nosal, Grażyna (Folia Toruniensia, 2020)
Thesis / Purpose: The aim of the article is to analyze the legends and biographies of saints for children published in Poland in the years 1945-1949. There are 19 items in the attached bibliography. Research method: The material was analyzed from autopsy on the basis of the copies preserved in the National Library (registered in the Polish bibliography of the Official Print List in Przewodnik Bibliograficzny). Results / Conclusions: Most of the items were published in Cracow and Warsaw in the years 1947-1948. Their authors were mostly well-known and respected secular writers, among whom Maria Kączkowska deserves special attention. Some texts had their pre-war editions. In legends and biographies, more than 50 people recognized by the Catholic Church as saints or dead were presented. Biographies, especially those of "holy children", were to constitute a role model for the young reader.